ANALYSIS OF FORMS OF SUPERVISION TO ANTICIPATE ABUSE OF AUTHORITY IN SUKAMULYA VILLAGE - FITRI VERDIANTI, LUTCHVIANA; Dunggio, Titin; S. Lakoro, Fibriyanti (Jurnal Ilmu Manajemen dan Bisnis, 2024)
The village is the legal body authorized to regulate and carry out governmental duties, in accordance with the provisions of Act No. 6 of 2014. A village can carry out its responsibilities independently by building an effective governance system. It requires high-quality human resources for leaders and employees. It is essential to carry out effective supervision during the performance of the assigned tasks in the village to avoid abuse of authority. The village government requires the highest level of rigour from the leadership and supervisory agencies to avoid abuse of authority. This can include actions such as giving warnings, performing performance evaluations, and reviewing administrative issues. In order for the activity plan to work smoothly, certain parties can supervise and enforce the authority used in the implementation of activities through effective monitoring mechanisms. The aim of this research is to gain an understanding of how surveillance is used to avoid abuse of authority in Suka Mulya Village. This research method is qualitative descriptive with observations, interviews and documentation as a method of data collection. The results of this study show that the monitoring and communication system in Suka Mulya Village is not optimal, which leads to a lack of effective communication between subordinates and superiors in the completion of activities, in addition there is lack of emphasis on the rigour of the leadership and supervisory bodies on the performance of the apparatus.